ANALISIS PERANAN SEKTOR INDUSTRI TERHADAP PEREKONOMIAN JAWA TENGAH TAHUN 2000 DAN TAHUN 2004 (ANALISIS INPUT OUTPUT) - Didit Purnomo; Devi Istiqomah (Muhammadiyah University Press, 2008)
This research aim to analyse role of industrial sector to other economy sectors in Central Java and the role in Central Java economy. Research method, which applied that, is Input Output Analysis Model (Analysis I-O), accompanied by analysis of role of production sector and output creator of Central Java economy, backward and forward linkage index analysis, and key sector analysis. Data which used that is I-O table of Central Java year 2000 and year 2004 with classification 19 sector is obtained from Central Java BPS. Research result indicate that industrial sector role is seen enough dominant in Central Java economy in the year 2000 and 2004. From the result, author suggests government so that more give priority to industrial sectors that become key sector in Central Java in the year 2000 and 2004.